Randomized investigator‐blinded comparative study of moisturizer containing 4‐t‐butylcyclohexanol and licochalcone A versus 0.02% triamcinolone acetonide cream in facial dermatitis - Boonchai, Waranya; Varothai, Supenya; Winayanuwattikun, Waranaree; Phaitoonvatanakij, Sutasinee; Chaweekulrat, Pichanee; Kasemsarn, Pranee (Journal of cosmetic dermatology, 2018)
Summary Background Facial dermatitis can result from various conditions, some of which are of a chronic and relapsing nature. The use of topical corticosteroid therapy may lead to additional adverse effects. Objective To compare the efficacy of moisturizer containing 4‐t‐butylcyclohexanol, which acts as a sensitivity regulator, and licochalcone A, an anti‐inflammatory agent from the licorice plant Glycyrrhiza inflata, with that of 0.02% triamcinolone acetonide (TA) for the treatment of facial dermatitis. Methods This was a randomized, prospective, investigator‐blinded study. Eighty participants with mild to moderate facial dermatitis were randomly treated with either the test facial moisturizer or 0.02% TA twice daily for the first 2 weeks. For the subsequent 2 weeks, all patients used only the test moisturizer. Clinical assessment by investigators, bioengineering measurements, patients' subjective evaluation, and clinical photography were performed at baseline, week 2, and week 4. Results Both treatments showed a statistically significant improvement with regard to physician clinical assessment, skin hydration, transepidermal water loss, and patient‐assessed visual analog scale after 2 and 4 weeks of treatment compared with baseline. The test facial moisturizer produced better skin hydration than TCS. The improvement in TEWL after 4 weeks of using the test moisturizer was comparable with 2‐week treatment with 0.02% TA cream. However, subjective evaluation by patients indicated that TA more rapidly improved sensation sensitivity. Conclusion The test facial moisturizer was slower than 0.02% TA in improving facial dermatitis, but showed greater benefit in erythema control and skin hydration.